(untitled) (Latakia University Journal -Biological Sciences Series, 2024)
The research aimed to identify the current reality of wheat production, and the reality of food security for wheat in Syria between the years 2011 and 2021. The area planted with wheat witnessed a clear decline, it was found that the availability of wheat was not constant, but rather decreased from 2013 to record its lowest value in 2016, when the available volume reached only 3,870 thousand tons, During the period between 2013-2021, the average growth rate reached about -1.7. The largest food gap for wheat was in 2021, when it reached about (-2456) thousand tons, due to the lack of production that year due to drought and the blockade, which resulted in the lack of fuel needed for irrigation. The amount of wheat available per capita for food also decreased from 172 kg annually in 2011 to reach 132 kg annually in 2016. The average per capita share of wheat during the period between 2011-2021 was estimated at about 142 kg annually. The availability of wheat per capita decreased at an average rate of -2.4. The lowest value for self-sufficiency was recorded in 2021, as it did not exceed 24.3%.